Іноземні мови у світовому економіко-правовому просторі. Вип. 11 : електронний збірник студентських наукових статей [Електронний ресурс] - (:unkn) unknown (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
У збірнику вміщено наукові статті студентів, які досліджують актуальні проблеми міжнародної економіки та міжнародних економічних відносин, туристичного бізнесу, реклами, PR і міжнародного права на матеріалі іншомовних публікацій. Для магістрантів і аспірантів.

The collection contains scientific articles by students who study topical issues of international economics, international relations and international economic relations, tourism business, environmental policy, international law, as well as the role of foreign languages in international cooperation based on foreign language publications. For undergraduate and postgraduate students.
Foreign languages in the world economic and legal space. Issue 11 : an electronic collection of student research articles [Electronic resource]
Keywords: HUMANITIES and RELIGION::Languages and linguistics::Linguistic subjects::Linguistics; SOCIAL SCIENCES::Business and economics; діджиталізація; екологічна політика; електронна комерція; Європейській Союз; імідж України; індустрія туризму; іноземні мови; інформаційна війна; кібербезпека; міжнародні відносини; міжнародні економічні відносини; російсько-українська війна; світова торгівля; cybersecurity; digitalization; e-commerce; environmental policy; dc.subject; image of Ukraine; information war; international relations; international economic relations; the European Union; the russian-ukrainian war; tourism industry; world trade